The village where Kudlich was born: Lobenstein (Schlesien), "der Wachberg mit der Kudlich-Warte". Here the ashes of Kudlich and his wife are kept
The village where Kudlich was born: Lobenstein (Schlesien), "der Wachberg mit der Kudlich-Warte". Here the ashes of Kudlich and his wife are kept.